IMPLEMENTATION OF LEADERSHIP ATTITUDE CHARACTER VALUES THROUGH SCOUT EXTRACURRICULAR ACTIVITIES AT SDN KANDANGAN - Novia Kartika Sari (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
The problem of education in education instilling leadership values in elementary schools needs to be studied, and alternative solutions are sought, and need to be developed more operational so that it is easy to apply in schools. Scouting extracurricular activities are one way to develop leadership character. Extracurricular activities are activities that are carried out in an organized manner by students both at the school and college levels outside of school hours. Extracurricular activities are carried out in order to develop personality, talents, and other abilities outside of academics with the aim of providing positive benefits for students. The type of research used is qualitative with a study approach. This research was used at SDN Kandangan. Based on the results of the research, the application of leadership character values carried out by scout leaders is to provide motivation and stimulation for students to have a high spirit of leadership and responsibility and to be able to develop knowledge with a variety of learning such as marching games, ceremonial practices and others so that students have a fairly good level of understanding. The research recommendations are directed at the role of scouts in instilling student character values through meaningful, interesting and challenging activities so that students are trained and accustomed to behaving well at school.